BRIDGING THE GAP: THE IMPACT OF E-SERVICE QUALITY AND USER TRUST ON LONG-TERM LOYALTY IN SHOPEE - Ila Karmila; Fadila Nurfauzia; Megah Dewi Anggini (Bina Ekonomi, 2026)
This study examines the impact of E-Service Quality and User Trust on long-term customer loyalty within the Shopee marketplace ecosystem in Indonesia. Using a quantitative explanatory approach, data were collected from 218 Generation Z respondents through structured online questionnaires. The analysis was conducted using multiple linear regression and path analysis with SPSS. The findings reveal that E-Service Quality has a positive and significant effect on long-term loyalty, while User Trust demonstrates a stronger and more dominant influence. Simultaneously, both variables significantly contribute to customer loyalty, explaining 63.9% of its variance. These results highlight that technical service performance alone is insufficient without building strong user trust. Therefore, enhancing system reliability, security, and transparency is essential for sustaining long-term customer relationships. This study provides both theoretical and practical contributions to digital marketing strategies in e-commerce platforms.